2001
DOI: 10.2307/2679924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salmon-Derived Nitrogen on Riparian Forest Growth and Implications for Stream Productivity

Abstract: Anadromous Pacific salmon (Oncorhynchus spp.) transport marine-derived nitrogen (MDN) to the rivers in which they reproduce. Isotopic analyses indicate that trees and shrubs near spawning streams derive ϳ22-24% of their foliar nitrogen (N) from spawning salmon. As a consequence of this nutrient subsidy, growth rates are significantly increased in Sitka spruce (Picea sitchensis) near spawning streams. As riparian forests affect the quality of instream habitat through shading, sediment and nutrient filtration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
171
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(178 citation statements)
references
References 24 publications
2
171
3
2
Order By: Relevance
“…The Carex C:N ratios in our study were not different in salmon and non-salmon streams. This contrasts with Helfield and Naiman (2001) who found that southeast Alaskan riparian trees had lower C:N ratios adjacent to streams with salmon than those without salmon spawners. However, Carex spp.…”
Section: C:n Ratios and Invertebrate Body Conditioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The Carex C:N ratios in our study were not different in salmon and non-salmon streams. This contrasts with Helfield and Naiman (2001) who found that southeast Alaskan riparian trees had lower C:N ratios adjacent to streams with salmon than those without salmon spawners. However, Carex spp.…”
Section: C:n Ratios and Invertebrate Body Conditioncontrasting
confidence: 91%
“…In contrast, invertebrates can obtain salmon-derived carbon and nitrogen by directly consuming salmon carcasses, and can also indirectly acquire salmon-derived nitrogen from isotopically enriched vegetation and herbivorous consumers (Hocking & Reimchen, 2002). Through these pathways, riparian plants and invertebrates alongside streams receiving salmon spawners often exhibit higher δ 15 N, but not necessarily higher δ 13 C (Ben- David et al, 1998;Bilby, Beach, Fransen, Walter, & Peter, 2003;Helfield & Naiman, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal migration has evolved as a complex behavior to enhance fitness and results from interactions between individuals (e.g., learned behavior), their genes, and the environment, notably spatiotemporal variation in resources and interspecific threats (e.g., predation; Dingle & Drake, 2007;Fryxell & Sinclair, 1988;Hebblewhite & Merrill, 2009). Migration is widespread across taxonomic groups and increasingly recognized as fundamental to maintaining populations and communities through effects on population productivity and the lateral transport of nutrients within and across ecosystems (Bolger, Newmark, Morrison, & Doak, 2008;Helfield & Naiman, 2001;Holdo, Holt, Sinclair, Godley, & Thirgood, 2011;Milner-Gulland, Fryxell, & Sinclair, 2011;Sawyer, Middleton, Hayes, Kauffman, & Monteith, 2016). Moreover, identifying and conserving migration corridors is an important management priority for state (WYGF, 2016) and federal (USDOI, 2018) agencies, and noted as one of the most difficult conservation challenges of the 21st century (Berger, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the best-known examples of this is the large-scale transport of marine carbon to freshwater and terrestrial ecosystems by migrating Pacific salmon, Oncorhynchus spp. (Helfield and Naiman 2001;Hocking and Reynolds 2011;Holtgrieve and Schindler 2011). Fishes may have a dual role: they prey on aquatic stages of terrestrial insects and thereby limit the transport of aquatic carbon to riparian plants and animals (Knight et al 2005;Finlay and Vredenburg 2007;Epanchin et al 2010;Hoekman et al 2011) but at the same time fishes augment transfers of terrestrial carbon into aquatic ecosystems via predation of terrestrial vertebrates and invertebrates (Fig.…”
Section: Introductionmentioning
confidence: 99%